Frequency and impact of grade three or four toxicities of novel agents on outcomes of older patients with chronic lymphocytic leukemia and non-Hodgkin lymphoma (alliance A151611). Issue 4 (July 2018) - Tallarico, Michael; Foster, Jared C.; Seisler, Drew; Lafky, Jacqueline M.; Hurria, Arti; Jatoi, Aminah; Cohen, Harvey J.; Muss, Hyman B.; Bartlett, Nancy; Cheson, Bruce D.; Jung, Sin-Ho; Leonard, John P.; et al.
Abstract: Objective: Older patients with cancer suffer from chemotherapy-related toxicities more frequently than younger patients. As novel agents are being used more commonly in chronic lymphocytic leukemia (CLL) and non-Hodgkin lymphoma (NHL), toxicities of these agents in older patients have not been well studied. Further, impact of these toxicities on outcomes in the elderly is unknown. This study aimed to answer both questions. Patients and Methods: We reviewed 14 Alliance for Clinical Trials in Oncology trials that enrolled CLL and/or NHL patients between 2004–2014. Toxicity was assessed per the NCI-CTCAE (version 3–5). Probabilities of experiencing grade three or four hematologic and non-hematologic toxicities were modeled as a function of clinical and disease-related factors using logistic regression. Results: 1199 patients (409 age ≥ 65; 790 age < 65) were analyzed; 438 received only biologic therapy (145 age ≥ 65; 293 age < 65), and 761 received biologic + chemotherapy (264 age ≥ 65; 497 age < 65). The odds of grade three or four hematologic [odds ratio (OR) 1.70; p  = 0.009: 95% CI (1.57–1.84)] and non-hematologic toxicities [OR 1.47; p  = 0.022; 95% CI (1.39–1.55)] were increased in older patients with CLL, as well as odds of grade three or four non-hematologic toxicities [OR 1.89; p  = 0.017; 95% CI (1.64–2.17)] in older patients with NHL. Grade three or four hematologic toxicities were associated with inferior OS and PFS in older patients with NHL [HR 3.14; p  = 0.006; 95% CI (2.25–4.39) for OS and 3.06; p  = 0.011; 95% CI (2.10–4.45) for PFS], though not in CLL. A prognostic model predicting grade three or four toxicities was also developed. Conclusions: CLL and NHL patients ≥ 65 year encounter more toxicities than younger patients even when treated with novel biologic agents. Development of grade three or four hematologic toxicities lead to inferior PFS and OS in NHL but not in CLL.